Spostrzeżenia i uwagi poczynione na podstawie wstępnej analizy zespołu , Prokuratoria Generalna RP w Warszawie’’ z lat 1919-1939 przechowywanego w Archiwum Akt Nowych w Warszawie. Przykłady wykorzystania do badania dziejów województwa lubelskiego - BANCERZ, Radosław (Historia i Świat, 2015)
Discussion about hard theme in years 1919-1939 The State Treasury Solicitors’ Office but giving many joys researcher. Acts allow to learn creation right law in II RP. I have described state of safe keeping of records gathered and stock in other archives concerning The State Treasury Solicitors. I have taken advantage available literature in my work, but it is not enough articles and publication on this theme work. However, personal observations are done during research been base of work. Researches had to show that possible find in this records in relation to province Lubelskie. It belongs to ascertain on base carried research, that group owns many interesting materials general concerning agricultural character province Lubelskie. First of all, they describe, archives describe relations among government officials and citizens. Otherwise, that allows to peer at questions from domain of rural economy in interwar period in the area Lubelskie. Article has to call attention as it says about office on purpose on meaning on acting administration The State Treasury Solicitors’ meeting of judicial authority among administration. I have described in concise form shortened manner for intent observing in forming describe operation role that right law The State Treasury Solicitors’ and relations administration -citizen. In article describes be that The State Treasury Solicitors Office (Prokuratoria Generalna Rzeczpospolitej Polskiej) and it serves examples can be for that archives useful.